Maatilojen lukumäärän muutos Suomessa 1995-2000 ja arvio vuoteen 2010 - Lehtonen, Heikki; Pietola, Kyösti; Niemi, Jarkko K. (MTT, 2002)
Structural development of Finnish agriculture, i.e. the number and size of farms in different agricultural production lines in Finland, is analysed using two methods. The first outlook simply continues the geometric average rate of change in farm numbers over the period of 1995-2000 forward in time until 2010. The period of 1995-2000 has been chosen for the basis of the projections since the economic environment of Finnish agriculture changed considerably in 1995. The number of farms decreased from 98,700 down to 78,400 in period 1995-2000. Second method relies on a regional sector model which simulates competitive behaviour of markets of agricultural products, including foreign trade of agricultural products, in a dynamic setting. Agricultural policy (EU price level, production quotas and agricultural supports), inflation of input prices, and price of labour are exogenous parameters in the model. The model also takes into account the fact that the production efficiency (use of labour and capital per hectare or animal) increases as the farm size grows, but the rate of efficiency improvement becomes slower as the farms become larger. The number of farms in period 1995-2000 declined by 4.5% annually, on the average. If the rate of change remains unchanged, the total number of farms will be 49,500 in year 2010. This is roughly 50% of the number of farms in 1995. The decrease in the number of farms was most rapid in Eastern Finland (5.4% annually) and in milk production (7.3% annually). If the rate remains unchanged, the number of dairy farms will decrease down to 10,600 farms at 2010. The sector model results show that if production quantities of some agricultural production lines are to be kept close to year 2000 levels, farm size needs to continue to grow at the same rate, or even at a slightly faster rate in some production lines, compared to the geometric average in the period of 1995-2000. This is due to expected decrease in the profitability of production caused by Agenda 2000 policy changes, and inflation of input prices. Since economic rationality is assumed in the model, the results show that the number of farms will decrease either because of increasing farm size or because of decreasing production volumes. According to the model, there will be roughly 38,000 farms in Finland in 2010. Horticultural production and lambs, however, are not included in the model. Hence the total number of farms will be larger than 40,000 in 2010. Furthermore, the results show that even if milk, pork and poultry meat production were to remain close to year 2000 production levels, there will be regional shifts in production. Some land will be abandoned in eastern and northern parts of the country. Beginning of this development has been pointed out in other studies. Overall, the results from both methods are consistent to each other and to other estimates of the number of farms in Finland.
Keywords: Ma; maatilojen lukumäärä; rakennekehitys; sektorimalli; geometrinen projektio; Suomi; maatilat; number of farms; Finland; structural development; sector model; geometric projection